Influences of the punched delta winglet vortex generators in a circular tube heat exchanger on thermo-hydraulic performance - Jedasadaratanachai, Withada; Boonloi, Amnart (My University, 2015)
Numerical investigations on flow topology, heat transfer behavior and thermal performance evaluation in a circular tube heat exchanger with the punched delta winglet vortex generators (PDWVG) inserted in the middle of the test section are presented. The effects of the flow attack angles that converging to the center of the tube; α = 0˚, 5˚, 10˚, 15˚, 20˚, 25˚, and flow directions; winglet tips pointing downstream and upstream, are investigated for the Reynolds numbers; Re = 100 – 2000. The finite volume method and SIMPLE algorithm are used for the current study. The results are presented in terms of flow configuration, heat transfer behavior and thermal performance assessments and also compared with the smooth tube with no PDWVG. As numerical results, the use of PDWVG inserted in the tube can help to improve heat transfer rate and thermal performance in the heat exchanger by creating the vortex flows through the test section. The rise of the flow attack angle and Reynolds number leads to increase in heat transfer, friction loss and thermal performance. The optimum TEF is around 2.33 at Re = 2000, α = 25˚ for winglet tip pointing downstream.
Keywords: Compact heat exchanger; Delta winglet; Laminar flow; Thermal enhancement factor